Ribosome-Associated Chloroplast SRP54 Enables Efficient Cotranslational Membrane Insertion of Key Photosynthetic Proteins. Issue 11 (23rd August 2019) - Hristou, Athina; Gerlach, Ines; Stolle, Dominique S.; Neumann, Jennifer; Bischoff, Annika; Dünschede, Beatrix; Nowaczyk, Marc M.; Zoschke, Reimo; Schünemann, Danja
Abstract : Ribosome profiling combined with biochemical studies demonstrates that chloroplast SRP54 contacts ribosomal uL4 and enhances cotranslational insertion of thylakoid membrane proteins. Abstract: Key proteins of the photosynthetic complexes are encoded in the chloroplast genome and cotranslationally inserted into the thylakoid membrane. However, the molecular details of this process are largely unknown. Here, we demonstrate by ribosome profiling that the conserved chloroplast signal recognition particle subunit (cpSRP54) is required for efficient cotranslational targeting of several central photosynthetic proteins, such as the PSII PsbA (D1) subunit, in Arabidopsis ( Arabidopsis thaliana ). High-resolution analysis of membrane-associated and soluble ribosome footprints revealed that the SRP-dependent membrane targeting of PsbA is already initiated at an early translation step before exposure of the nascent chain from the ribosome. In contrast to cytosolic SRP, which contacts the ribosome close to the peptide tunnel exit site, analysis of the cpSRP54/ribosome binding interface revealed a direct interaction of cpSRP54 and the ribosomal subunit uL4, which is not located at the tunnel exit site but forms a part of the internal peptide tunnel wall by a loop domain. The plastid-specific C-terminal tail region of cpSRP54 plays a crucial role in uL4 binding. Our data indicate a novel mechanism of SRP-dependent membrane protein transport with the cpSRP54/uL4 interaction as a central element in early initiation of cotranslational membrane targeting.